ANALISIS KONTEN KOMIK SEBAGAI SARANA KRITIK SOSIAL DAN LITERASI DIGITAL DALAM @MAJALAH.TEMPO - Rizky Adelia Br. Hombing; Zahra Arifa; Kristina Apri Jaya Sinaga (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to analyze the role of digital comics published by the Instagram account @majalah.tempo as a means of social criticism and increasing public digital literacy. In today's digital era, comics not only function as a medium of entertainment, but also as a tool to convey complex social and political messages in a creative and easy-to-understand way. This research uses the content analysis method to explore how these comics represent political and social issues in Indonesia, as well as their effectiveness in improving people's digital literacy. Through the analysis of four comics published in February 2025, this study found that the comics are effective in criticizing government policies and raising public awareness of social issues. In addition, this study also identified factors that influence audience acceptance of comic content, including visual style and the relevance of the issues raised. The results of this study are expected to make a significant contribution to communication studies as well as assist content creators and educators in developing more effective communication strategies through comic media.